Method for preparing lithium-rich manganese-based positive electrode material by using auxiliary complexing agent with high capacity and cycling stability

By using ethylenediaminetetraacetic acid (EDTA) as an auxiliary complexing agent to improve the crystallinity and lattice spacing of lithium-rich manganese-based cathode materials and form a protective layer, the problem of poor cycle stability of lithium-rich manganese-based cathode materials is solved, and high capacity and cycle performance are improved.

CN120841587APending Publication Date: 2025-10-28XIAN TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510994364.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-18
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Lithium-rich manganese-based cathode materials suffer from poor cycle stability during charge and discharge, resulting in severe capacity decay and hindering commercial application.

Method used

Ethylenediaminetetraacetic acid (EDTA) is used as an auxiliary complexing agent. By forming stable chelates with metal ions, it improves the crystallinity and lattice spacing of the material, forms three-dimensional Li+ diffusion channels, and generates a protective layer on the material surface to avoid side reactions between the electrode and the electrolyte.

Benefits of technology

It improves the cycle stability and electrochemical performance of the material, enhances the lithium-ion transport rate and the charge/discharge speed of the battery, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120841587A_ABST
    Figure CN120841587A_ABST
Patent Text Reader

Abstract

A method for preparing a lithium-rich manganese-based positive electrode material by using an auxiliary complexing agent with high capacity and cycling stability comprises the following steps: adding lithium acetate, nickel acetate, cobalt acetate and manganese acetate into deionized water, uniformly mixing to form a metal salt solution, adding an auxiliary complexing agent ethylenediamine tetraacetic acid, adding a citric acid monohydrate complexing agent at the same time, and uniformly mixing to form a lithium-rich manganese-based positive electrode material; uniformly stirring to obtain a precursor salt solution with the ethylenediamine tetraacetic acid concentration of 0.4 g / L-1. 2g / L; performing spray pyrolysis on the precursor salt solution to prepare precursor powder; and placing the precursor powder in a muffle furnace for high-temperature calcination treatment to obtain modified lithium-rich manganese-based positive electrode material powder. The preparation method has the advantages that the process is simple, the lattice spacing of the material can be improved, a more stable coordination structure can be formed, a protective layer is formed on the surface of the material, and side reaction between an electrode and electrolyte is avoided, so that the stability of the material is improved, and the capacity and the cycle performance are jointly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery cathodes, specifically relating to a method for preparing lithium-rich manganese-based cathode materials using an auxiliary complexing agent that combines high capacity and cycle stability. Background Technology

[0002] With rapid societal development, energy demand is increasing daily, making traditional primary energy sources insufficient for sustainable human development. Lithium-ion rechargeable batteries, as a new type of portable energy storage device, are widely used in energy storage fields such as consumer electronics, electric vehicles, and microgrids. Lithium-ion batteries mainly consist of a positive electrode, a negative electrode, a separator, and an electrolyte. The characteristics of the positive electrode material play a crucial role in determining the overall performance of the lithium-ion battery.

[0003] Lithium-rich manganese-based cathode materials have attracted much attention from academia and industry due to their high energy density characteristics caused by their unique charge compensation mechanism. However, the anion redox process during charging and discharging, although the source of high energy density, causes many problems, adversely affecting cycle stability, resulting in severe capacity decay and hindering commercial application.

[0004] Currently, to improve the cycle stability of lithium-rich manganese-based cathode materials to meet the demands of large-scale applications, common modification methods include surface modification and element doping. For element doping, conventional salts such as nitrates, acetates, and chlorides are often used. The insertion and extraction of lithium ions in cathode materials depends on appropriate lattice spacing. After conventional modification, the lattice spacing of the material does not change significantly, and may even decrease due to lattice distortion. This causes significant resistance to lithium ion transport, reducing the transport rate. This not only limits the battery's charge and discharge speed but also prevents lithium ions from efficiently participating in electrochemical reactions, hindering the full utilization of battery capacity. Furthermore, after multiple cycles, the uneven accumulation and consumption of lithium ions further exacerbates capacity decay, severely impacting cycle performance. Furthermore, during charge-discharge cycles, the crystal structure of lithium-rich manganese-based cathode materials continuously changes. Materials lacking stable coordination structures cannot effectively resist the stress caused by these structural changes, easily leading to phenomena such as lattice collapse and particle breakage. This not only disrupts lithium-ion transport channels, causing a rapid decrease in battery capacity, but also increases the contact area between the electrode and the electrolyte, triggering more side reactions and further deteriorating cycle performance. In addition, during battery charge-discharge, the electrode material is in direct contact with the electrolyte, easily resulting in redox reactions that consume active materials and electrolyte, while generating byproducts such as gases and precipitates. These byproducts accumulate on the electrode surface, hindering lithium-ion transport, increasing battery internal resistance, and leading to capacity decay and shortened cycle life. Therefore, there is an urgent need to develop a method for preparing lithium-rich manganese-based cathode materials that can effectively enhance their cycle stability while improving capacity, achieving a balance between capacity and cycle performance, to promote the commercial application of lithium-rich manganese-based cathode materials in the field of lithium-ion batteries. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing lithium-rich manganese-based cathode materials with an auxiliary complexing agent that has both high capacity and cycle stability. The process is simple, can improve the lattice spacing of the material, form a more stable coordination structure, and form a protective layer on the surface of the material to avoid side reactions between the electrode and the electrolyte, thereby improving the stability of the material and achieving a joint improvement in capacity and cycle performance.

[0006] To achieve the above object, the technical solution provided by the present invention is: A method for preparing lithium-rich manganese-based cathode materials using an auxiliary complexing agent, the specific steps of which are as follows: Step 1: Prepare the precursor salt solution: Lithium acetate, nickel acetate, cobalt acetate, and manganese acetate were added to deionized water and mixed evenly to form a metal salt solution. Ethylenediaminetetraacetic acid (EDTA) was added as an auxiliary complexing agent, and citric acid monohydrate complexing agent was added at the same time. The mixture was stirred evenly to obtain a precursor salt solution with an EDTA concentration of 0.4 g / L-1.2 g / L. Step 2: Preparation of precursor powder: Precursor powder was prepared by spray pyrolysis of precursor salt solution; Step 3: Preparation of modified lithium-rich manganese-based cathode materials: The precursor powder was calcined at high temperature in a muffle furnace to obtain modified lithium-rich manganese-based cathode material powder.

[0007] Furthermore, the concentration of the monohydrated citric acid complexing agent in the precursor salt solution is 0.6 mol / L.

[0008] Furthermore, the total concentration of lithium acetate, nickel acetate, cobalt acetate and manganese acetate in the metal salt solution is 0.6 mol / L.

[0009] More preferably, the molar ratio of the lithium acetate, nickel acetate, cobalt acetate and manganese acetate is 3.7:0.4:0.4:1.6.

[0010] Furthermore, the modified lithium-rich manganese-based cathode material powder is a lithium-rich manganese-based cathode material of Li. 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

[0011] Furthermore, in step one, the stirring speed is 400 r / min and the stirring time is 2 hours.

[0012] Furthermore, in step two, during the spray drying process, the liquid inlet rate is 10 mL / min, the inlet and outlet temperatures are set to 230℃ and 120℃ respectively, and the peristaltic speed is set to 20 rpm.

[0013] Furthermore, in step three, the high-temperature calcination is carried out at a temperature of 1000℃ for 20 minutes, followed by natural cooling to room temperature.

[0014] Further optimization is that during high-temperature calcination, the heating rate is 3℃ / min.

[0015] Furthermore, the concentration of ethylenediaminetetraacetic acid in the precursor salt solution was 0.8 g / L.

[0016] The beneficial effects of this invention are: (1) Lithium-rich manganese-based cathode materials were prepared using ethylenediaminetetraacetic acid (EDTA) as an auxiliary complexing agent. The strong complexing effect of EDTA on transition metal ions improved the crystallinity of the material and reduced Li / Ni mixing. The lattice of the material prepared by the auxiliary complexation slightly expanded, increasing the Li... + Transport channels, good crystallinity and expanded Li + Channels can help improve overall electrochemical performance.

[0017] (2) The ethylenediaminetetraacetic acid used in this invention contains two amino nitrogen groups and four carboxyl oxygen groups, which can form stable chelates with metal ions. The coordinating atoms have a certain spatial arrangement and can form a stable ring structure with metal ions. The capacity retention rate can reach 80.29% after 400 cycles at 1C current. Although chelate structures can also be formed by complexing with a single citric acid, the number of chelate structures formed is relatively small and the stability is poor.

[0018] (3) This invention prepares lithium-rich manganese-based cathode materials through ethylenediaminetetraacetic acid-assisted complexation, resulting in the in-situ formation of a spinel phase on the material, forming a three-dimensional Li + The diffusion channels provide more pathways and space for lithium-ion migration, lowering the energy barrier for lithium-ion diffusion and thus improving the rate performance of the material, achieving a discharge specific capacity of 130.43 mAh·g at a 10C current density. -1 Transmission electron microscopy reveals that the spinel structure is distributed on the surface of the material, forming a protective layer that can effectively prevent side reactions between the positive electrode and the electrolyte, thereby reducing interfacial resistance and improving cycle stability. Attached Figure Description

[0019] Figure 1 The images shown are XRD patterns before cycling of the present invention (corresponding to Embodiment 1, Embodiment 2, Embodiment 3 and Comparative Example 1); Figure 2 The XPS images are shown before cycling in the present invention (corresponding to Example 2 and Comparative Example 1); Figure 3 These are SEM images of the present invention (corresponding to Embodiment 1, Embodiment 2, Embodiment 3 and Comparative Example 1); Figure 4 The diagrams show the HRTEM image before cycling in the present invention (corresponding to Example 2 and Comparative Example 1) and the mapping image in the present invention (corresponding to Example 2). Figure 5 The images show a comparison of the first charge and discharge cycles at 0.1C for the present invention (corresponding to Examples 1-3 and Comparative Examples 1-4). Figure 6 This is a comparison chart of the rate performance of the present invention (corresponding to Examples 1-3 and Comparative Examples 1-4); Figure 7This is a comparison diagram of the 1C cycle of the present invention (corresponding to Examples 1-3 and Comparative Examples 1-4); Figure 8 This is a comparison diagram of the pre-cycle impedance of the present invention (corresponding to Embodiment 1, Embodiment 2, Embodiment 3 and Comparative Example 1); Figure 9 This is a comparison chart of the HRTEM after 200 cycles at 1C for the present invention (corresponding to Example 2 and Comparative Example 1). Detailed Implementation

[0020] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0021] Example 1 Step 1: Prepare the precursor solution Weigh out 38.1963 g of lithium acetate dihydrate, 9.7048 g of nickel acetate tetrahydrate, 9.7141 g of cobalt acetate tetrahydrate, and 39.7046 g of manganese acetate tetrahydrate, dissolve them in 1 L of deionized water, add 126.084 g of citric acid monohydrate as a complexing agent, and add 0.4 g of ethylenediaminetetraacetic acid as an auxiliary complexing agent. Place the mixture in a magnetic stirrer and stir at 400 r / min for 2 h to obtain the precursor solution. Step 2: Preparation of precursor powder The precursor solution was granulated by spray drying at a feed rate of 10 mL / min, an inlet air temperature of 230℃, an outlet air temperature of 120℃, and a peristaltic speed of 20 rpm to obtain precursor powder. Step 3: Preparation of modified lithium-rich manganese-based cathode materials The precursor powder was placed in an alumina crucible and heated to 1000°C in a box furnace at a rate of 3°C / min. The temperature was held at 1000°C for 20 min, and then naturally cooled to room temperature to obtain the modified lithium-rich manganese-based cathode material Li. 1.2 Co 0.13 Ni 0.13 Mn 0.54 O2.

[0022] Example 2 The difference in this embodiment is that the amount of ethylenediaminetetraacetic acid added in step 1 is 0.8g, while the rest is the same as in embodiment 1.

[0023] Step 1: Prepare the precursor solution Weigh out 38.1963 g of lithium acetate dihydrate, 9.7048 g of nickel acetate tetrahydrate, 9.7141 g of cobalt acetate tetrahydrate and 39.7046 g of manganese acetate tetrahydrate and dissolve them in 1 L of deionized water. Add 126.084 g of citric acid monohydrate as a complexing agent and 0.8 g of ethylenediaminetetraacetic acid as an auxiliary complexing agent. Place the mixture in a magnetic stirrer and stir at 400 r / min for 2 h to obtain the precursor solution. Step 2: Preparation of precursor powder The precursor solution was granulated by spray drying at a feed rate of 10 mL / min, an inlet air temperature of 230℃, an outlet air temperature of 120℃, and a peristaltic speed of 20 rpm to obtain precursor powder. Step 3: Preparation of modified lithium-rich manganese-based cathode materials The precursor powder was placed in an alumina crucible and heated to 1000°C in a box furnace at a rate of 3°C / min. The temperature was held at 1000°C for 20 min, and then naturally cooled to room temperature to obtain the modified lithium-rich manganese-based cathode material Li. 1.2 Co 0.13 Ni 0.13 Mn 0.54 O2.

[0024] Example 3 The difference in this embodiment is that the amount of ethylenediaminetetraacetic acid added in step 1 is 1.2g, while the rest is the same as in embodiment 2.

[0025] Step 1: Prepare the precursor solution Weigh out 38.1963 g of lithium acetate dihydrate, 9.7048 g of nickel acetate tetrahydrate, 9.7141 g of cobalt acetate tetrahydrate and 39.7046 g of manganese acetate tetrahydrate and dissolve them in 1 L of deionized water. Add 126.084 g of citric acid monohydrate as a complexing agent and 1.2 g of ethylenediaminetetraacetic acid as an auxiliary complexing agent. Place the mixture in a magnetic stirrer and stir at 400 r / min for 2 h to obtain the precursor solution. Step 2: Preparation of precursor powder The precursor solution was granulated by spray drying at a feed rate of 10 mL / min, an inlet air temperature of 230℃, an outlet air temperature of 120℃, and a peristaltic speed of 20 rpm to obtain precursor powder. Step 3: Preparation of modified lithium-rich manganese-based cathode materials The precursor powder was placed in an alumina crucible and heated to 1000°C in a box furnace at a rate of 3°C / min. The temperature was held at 1000°C for 20 min, and then naturally cooled to room temperature to obtain the modified lithium-rich manganese-based cathode material Li. 1.2 Co 0.13 Ni 0.13 Mn 0.54 O2.

[0026] Comparative Example 1 The difference in this comparative example is that ethylenediaminetetraacetic acid is not added in step 1; otherwise, it is the same as in Example 1.

[0027] Step 1: Prepare the precursor solution Weigh out 38.1963 g of lithium acetate dihydrate, 9.7048 g of nickel acetate tetrahydrate, 9.7141 g of cobalt acetate tetrahydrate and 39.7046 g of manganese acetate tetrahydrate, dissolve them in 1 L of deionized water, add 126.084 g of citric acid monohydrate as a complexing agent, place in a magnetic stirrer, and stir at 400 r / min for 2 h to obtain the precursor solution; Step 2: Preparation of precursor powder The precursor solution was granulated by spray drying at a feed rate of 10 mL / min, an inlet air temperature of 230℃, an outlet air temperature of 120℃, and a peristaltic speed of 20 rpm to obtain precursor powder. Step 3: Preparation of modified lithium-rich manganese-based cathode materials The precursor powder was placed in an alumina crucible and heated to 1000°C in a box furnace at a rate of 3°C / min. The temperature was held at 1000°C for 20 min, and then naturally cooled to room temperature to obtain the modified lithium-rich manganese-based cathode material Li. 1.2 Co 0.13 Ni 0.13 Mn 0.54 O2.

[0028] Comparative Example 2 The difference in this comparative example is that 2g of ethylenediaminetetraacetic acid was added in step 1, otherwise it is the same as in Example 3.

[0029] Step 1: Prepare the precursor solution Weigh out 38.1963 g of lithium acetate dihydrate, 9.7048 g of nickel acetate tetrahydrate, 9.7141 g of cobalt acetate tetrahydrate and 39.7046 g of manganese acetate tetrahydrate and dissolve them in 1 L of deionized water. Add 126.084 g of citric acid monohydrate as a complexing agent and 2 g of ethylenediaminetetraacetic acid as an auxiliary complexing agent. Place the mixture in a magnetic stirrer and stir at 400 r / min for 2 h to obtain the precursor solution. Step 2: Preparation of precursor powder The precursor solution was granulated by spray drying at a feed rate of 10 mL / min, an inlet air temperature of 230℃, an outlet air temperature of 120℃, and a peristaltic speed of 20 rpm to obtain precursor powder. Step 3: Preparation of modified lithium-rich manganese-based cathode materials The precursor powder was placed in an alumina crucible and heated to 1000°C in a box furnace at a rate of 3°C / min. The temperature was held at 1000°C for 20 min, and then naturally cooled to room temperature to obtain the lithium-rich manganese-based cathode material Li. 1.2 Co 0.13 Ni 0.13 Mn 0.54 O2.

[0030] Comparative Example 3 The difference in this comparative example is that aminosulfonic acid is used instead of ethylenediaminetetraacetic acid in step 1, otherwise it is the same as in Example 2.

[0031] Step 1: Prepare the precursor solution Weigh out 38.1963 g of lithium acetate dihydrate, 9.7048 g of nickel acetate tetrahydrate, 9.7141 g of cobalt acetate tetrahydrate and 39.7046 g of manganese acetate tetrahydrate and dissolve them in 1 L of deionized water. Add 126.084 g of citric acid monohydrate as a complexing agent and 0.8 g of aminosulfonic acid as an auxiliary complexing agent. Place the mixture in a magnetic stirrer and stir at 400 r / min for 2 h to obtain the precursor solution. Step 2: Preparation of precursor powder The precursor solution was granulated by spray drying at a feed rate of 10 mL / min, an inlet air temperature of 230℃, an outlet air temperature of 120℃, and a peristaltic speed of 20 rpm to obtain precursor powder. Step 3: Preparation of modified lithium-rich manganese-based cathode materials The precursor powder was placed in an alumina crucible and heated to 1000°C in a box furnace at a rate of 3°C / min. The temperature was held at 1000°C for 20 min, and then naturally cooled to room temperature to obtain the modified lithium-rich manganese-based cathode material Li. 1.2 Co 0.13 Ni 0.13 Mn 0.54 O2.

[0032] Comparative Example 4 The difference in this comparative example is that citric acid monohydrate is used instead of ethylenediaminetetraacetic acid in step 1, otherwise it is the same as in Example 2.

[0033] Step 1: Prepare the precursor solution Weigh out 38.1963 g of lithium acetate dihydrate, 9.7048 g of nickel acetate tetrahydrate, 9.7141 g of cobalt acetate tetrahydrate and 39.7046 g of manganese acetate tetrahydrate, dissolve them in 1 L of deionized water, add 126.884 g of citric acid monohydrate as a complexing agent, place in a magnetic stirrer, and stir at 400 r / min for 2 h to obtain the precursor solution; Step 2: Preparation of precursor powder The precursor solution was granulated by spray drying at a feed rate of 10 mL / min, an inlet air temperature of 230℃, an outlet air temperature of 120℃, and a peristaltic speed of 20 rpm to obtain precursor powder. Step 3: Preparation of modified lithium-rich manganese-based cathode materials The precursor powder was placed in an alumina crucible and heated to 1000°C in a box furnace at a rate of 3°C / min. The temperature was held at 1000°C for 20 min, and then naturally cooled to room temperature to obtain the modified lithium-rich manganese-based cathode material Li. 1.2 Co 0.13 Ni 0.13 Mn 0.54 O2.

[0034] I. Physicochemical Performance Testing of the Embodiments and Comparative Example Products of the Invention The XRD comparison diagrams before cycling of Comparative Example 1 and Examples 1-3 of the present invention are shown below. Figure 1 As shown, by Figure 1 The peak shapes are consistent before and after the addition of ethylenediaminetetraacetic acid (EDTA), with no obvious impurity peaks, indicating that EDTA does not affect the structure of the lithium-rich manganese-based cathode material. The difference lies in the increasing 003 / 104 ratio with the addition of EDTA, indicating improved orderliness. This suggests that appropriate orderliness is beneficial for enhancing electrochemical performance. Simultaneously, the 003 peak gradually shifts to a lower angle, indicating an increase in the c-axis, which means that the increased interlayer spacing expands the Li+ diffusion channels and improves Li+ diffusion. + Diffusion capability helps maintain the integrity of the material structure and improves cycle stability.

[0035] XPS plots before cycling for Comparative Example 1 and Example 2 of this invention are shown below. Figure 2 As shown, by Figure 2 (Left) As can be seen, after modification with ethylenediaminetetraacetic acid, the trivalent manganese significantly increases. The increase in low-valence transition metals is beneficial for providing more charge compensation and enhancing the reversible capacity of the electrode. Figure 2 (Right) It can be seen that there is no obvious peak at the binding energy of around 400 eV, indicating that the content of N element introduced from ethylenediaminetetraacetic acid in the modified sample is relatively small, which helps to reduce the side reactions that may be caused by the introduction of other elements.

[0036] The SEM images of Comparative Example 1 and Examples 1-3 before cycling are shown below. Figure 3 As shown, by Figure 3 As can be seen, the particle size and morphology of the sample after the addition of ethylenediaminetetraacetic acid (EDTA) did not change significantly, indicating that EDTA-assisted complexation does not change the particle size and morphology.

[0037] The HRTEM plots of Comparative Example 1 and Example 2 before cycling and the Mapping plot of Example 2 are shown below. Figure 4 As shown, by Figure 4As can be seen, the particle size did not change significantly after the addition of ethylenediaminetetraacetic acid (EDTA). A spinel phase appeared on the surface of the modified sample, which is beneficial for improving rate performance. The lattice spacing increased slightly, which helps to improve Li... + Diffusion enhances electrochemical performance. Mapping data shows that elements are evenly distributed in the modified sample. XPS analysis also shows that the modified sample contains a small amount of evenly distributed nitrogen, which helps reduce side reactions that may be caused by the introduction of foreign elements.

[0038] The initial charge-discharge curves of Comparative Examples 1-4 and Examples 1-3 of the present invention are as follows: Figure 5 As shown, by Figure 5 It can be seen that Example 2 has the largest initial discharge capacity at 0.1C, which is 301.96mAh / g.

[0039] The rate performance test graphs of Comparative Examples 1-4 and Examples 1-3 of this invention are shown below. Figure 6 As shown, by Figure 6 It can be seen that Example 2 has the best performance at the magnification.

[0040] The comparison graph of the cycle performance of Comparative Examples 1-4 and Examples 1-3 of this invention is shown in the figure below. Figure 7 As shown, by Figure 7 It can be seen that Example 2 has the best cycle performance at 1C.

[0041] The pre-cycle impedance comparison diagrams of Comparative Example 1 and Examples 1-3 of the present invention are shown below. Figure 8 As shown, by Figure 8 It can be seen that the impedance of Example 2 is the lowest before the cycle.

[0042] The HRTEM images of Comparative Example 1 and Example 2 after 200 cycles are shown below. Figure 9 As shown, by Figure 9 It can be seen that the thickness of the CEI film in Comparative Example 1 after cycling is about 2.8 nm, and the thickness of the CEI film in Example 2 is about 2.3 nm. The modified sample generated a thinner CEI film during cycling, which is beneficial to the transport of lithium ions.

[0043] II. ICP detection in Example 2 and Comparative Example 1 of the present invention As shown in Table 1, the ICP test results for Comparative Example 1 and Example 2 are as follows: Table 1 Table 1 shows that the contents of Li, Ni, Co, and Mn are basically in line with the theoretical values. Figure 1 XRD analysis revealed that the synthesized material conformed to the characteristic peaks of C2 / m and R-3m, therefore it was considered that Li was synthesized. 1.2 Ni0.13 Co 0.13 Mn 0.54 O2.

[0044] The modified lithium-rich manganese-based cathode materials, Super P powder, and a 1.2% (w / w) CMC aqueous solution prepared in Examples 1-3 and Comparative Examples 1-4 were mixed in a mass ratio of 253:32:1250. After ball milling for 4 hours, the mixture was coated onto aluminum foil and vacuum dried at 110°C for 20 hours. After cutting, it was vacuum dried again for 10 hours and then transferred into a glove box for assembling coin cells. Tests were conducted, and the results are shown in Table 2. Table 2 As shown in Table 2, adding a small amount of ethylenediaminetetraacetic acid (EDTA) in Example 1 significantly affected the performance; continued addition in Example 2 slightly improved the performance; excessive addition in Comparative Example 2 resulted in a decrease in performance; the addition of another auxiliary complexing agent, aminosulfonic acid, also led to a decrease in performance, as shown in Comparative Example 3. Replacing aminosulfonic acid with an equal amount of citric acid did not significantly improve the performance, as shown in Comparative Example 4. Example 2 exhibited the best performance, with a capacity retention of 80.29% after 400 cycles at 1C.

[0045] The above are merely specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing lithium-rich manganese-based cathode materials using an auxiliary complexing agent, characterized in that: The specific steps are as follows: Step 1: Prepare the precursor salt solution: Lithium acetate, nickel acetate, cobalt acetate, and manganese acetate were added to deionized water and mixed evenly to form a metal salt solution. Ethylenediaminetetraacetic acid (EDTA) was added as an auxiliary complexing agent, and citric acid monohydrate complexing agent was added at the same time. The mixture was stirred evenly to obtain a precursor salt solution with an EDTA concentration of 0.4 g / L-1.2 g / L. Step 2: Preparation of precursor powder: Precursor powder was prepared by spray pyrolysis of precursor salt solution; Step 3: Preparation of modified lithium-rich manganese-based cathode materials: The precursor powder was calcined at high temperature in a muffle furnace to obtain modified lithium-rich manganese-based cathode material powder.

2. The method for preparing lithium-rich manganese-based cathode materials using the auxiliary complexing agent according to claim 1, characterized in that: The concentration of the monohydrated citric acid complexing agent in the precursor salt solution is 0.6 mol / L.

3. The method for preparing lithium-rich manganese-based cathode materials using the auxiliary complexing agent according to claim 1, characterized in that: The total concentration of lithium acetate, nickel acetate, cobalt acetate and manganese acetate in the metal salt solution is 0.6 mol / L.

4. The method for preparing lithium-rich manganese-based cathode materials using the auxiliary complexing agent according to claim 3, characterized in that: The molar ratio of the acetates of lithium, nickel, cobalt, and manganese is 3.7:0.4:0.4:1.

6.

5. The method for preparing lithium-rich manganese-based cathode materials using the auxiliary complexing agent according to claim 1, characterized in that: The modified lithium-rich manganese-based cathode material powder is a lithium-rich manganese-based cathode material of Li. 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.

6. The method for preparing lithium-rich manganese-based cathode materials using the auxiliary complexing agent according to claim 1, characterized in that: In step one, the stirring speed is 400 r / min and the stirring time is 2 hours.

7. The method for preparing lithium-rich manganese-based cathode materials using the auxiliary complexing agent according to claim 1, characterized in that: In step two, during the spray drying process, the liquid inlet rate is 10 mL / min, the inlet and outlet temperatures are set to 230℃ and 120℃ respectively, and the peristaltic speed is set to 20 rpm.

8. The method for preparing lithium-rich manganese-based cathode materials using the auxiliary complexing agent according to claim 1, characterized in that: In step three, the high-temperature calcination is carried out at a temperature of 1000℃ for 20 minutes, followed by natural cooling to room temperature.

9. The method for preparing lithium-rich manganese-based cathode materials using the auxiliary complexing agent according to claim 8, characterized in that: During high-temperature calcination, the heating rate is 3℃ / min.

10. The method for preparing lithium-rich manganese-based cathode materials using the auxiliary complexing agent according to claim 1, characterized in that: The concentration of ethylenediaminetetraacetic acid in the precursor salt solution was 0.8 g / L.